Dynamics of dry matter and selenium accumulation in oilseed rape (Brassica napus L.) in response to organic and inorganic selenium treatments - Ebrahimi, Nashmin; Hartikainen, Helinä; Simojoki, Asko; Hajiboland, Roghieh; Seppänen, Mervi M (Agricultural and food science, 2015)
The uptake by and subsequent translocation of selenium (Se) within the plant is dependent on its chemical from and soil properties that dictate this trace element’s bioavailability. Plant species differ in their tendency to accumulate Se. Se taken-up by plants is returned to soil in plant residues, but the bioavailability of organic Se in those residues is poorly known. We investigated the impact of inorganic (Na2SeO4), organic (Se-enriched stem and leaf residues) Se applications and also soil microbial respiration on the growth and Se concentrations of various plant organs of oilseed rape (Brassica napus L.) during its development from the rosette to the seed filling stage. Both inorganic and organic Se slightly improved plant growth and enhanced plant development. Inorganic Se was more bioavailable than the organic forms and resulted in 3-fold to 6-fold higher Se concentrations in the siliques. Inorganic Se in autoclaved soil tended to elevate the Se concentration in all plant parts and at all growth stages. The organic Se raised Se concentrations in plants much less effectively than the inorganic selenate. Therefore, the use of inorganic Se is still recommended for biofortification.